Kepastian Hukum Penyelesaian Sengketa Dengan Klausula Arbitrase Di Mahkamah Agung - Fitri, Devianty; Almaududi, Almaududi (Jurnal Hukum & Pembangunan, 2023)
Settling disputes in court can be a time-consuming and exhausting process. Therefore, the availability of arbitration as an Alternative Dispute Resolution (ADR) is one of the efforts to achieve faster solutions and dispute resolutions. However, in some cases in the Supreme Court, there are disputes that contain arbitration clauses in the agreement, yet they are still submitted to court and decided by the court. This research aims to examine the disappearing in-depth study of legal certainty in dispute resolution with arbitration clauses by analyzing several verdicts. The method used in this study is normative juridical with a legislative and case approach. The research results show that in reality, even if an agreement is made with an arbitration clause, the parties still file a lawsuit in the general court on the pretext of unlawful acts and/or the involvement of third parties outside the agreement